Assessing the degeneration of cassava under high-virus inoculum conditions in coastal Tanzania - Shirima, R.R.; Maeda, D.G.; Kanju, E.E.; Tumwegamire, Silver; Ceasar, G.; Mushi, E.; Sichalwe, C.; Mtunda, K.; Mkamilo, G.; Legg, James P. (Scientific Societies, 2019)
Cassava brown streak disease (CBSD), caused by cassava brown streak ipomoviruses (CBSIs), has become the most debilitating biotic stress to cassava production in East and Central Africa. Lack of CBSD-resistant varieties has necessitated the search for alternative control measures. Most smallholder farmers reuse stems from previous crops for planting in the new season. Recycling planting material in this way can lead to “degeneration” owing to the compounding effects of disease. In this study, degeneration was defined as the increase in CBSD incidence and reduction in marketable root yield over time. An experiment was established to study the rates of degeneration in selected cassava varieties Chereko, KBH2002_135, Kipusa, Kizimbani, and Mkuranga1 and cultivars Kiroba and Kikombe under high-CBSD inoculum conditions in Bagamoyo, Tanzania from 2013 to 2017. The experiment was replicated across two seasons: the first planted during the long rains (Masika) between March and June and the second planted during the short rains (Vuli) between October and December. Mean abundance of the whitefly vector (Bemisia tabaci) was much greater during the Vuli season (>19 insects per plant) than the Masika season (<2 insects per plant). CBSD shoot symptoms occurred naturally and were observed only on Kikombe, Kiroba, and Kipusa. New materials had overall lower CBSD shoot incidences (1.5%) compared with recycled materials (6.9%) in Masika, although no significant differences were obvious in Vuli. However, Masika (8.7%) had an overall lower CBSD shoot incidence than Vuli (16.5%) in the varieties that had shoot symptoms. CBSD root incidences were higher in Vuli (10.3%) than Masika (4.4%), and root yields in Masika (29.4 t/ha) were significantly greater than those in Vuli (22.5 t/ha). The highest percentage of roots rendered unusable owing to CBSD was observed in Vuli. There was significantly higher unusable root incidence in recycled materials (3.7%) than in new materials (1.4%) in Masika but not in Vuli. Overall root yield was similar between recycled and new materials in either season. Significant reductions in root yield over the course of the experiment were observed both in Masika and Vuli, whereas changes in marketable yield were significant only in Masika. Differences in the response of varieties to degeneration led to the identification of four degeneration patterns, namely “strong,” “moderate,” “mild,” and “delayed” degeneration. The strongest effects of degeneration were most obvious in the susceptible cultivar (Kikombe), which also had the lowest marketable yield in either season. Seasonal differences were a key driver of degeneration, because its effects were much greater in Vuli than Masika. To the best of our knowledge, this work reports the first study of degeneration caused by cassava viruses.